OBSTACLE AVOIDER PROTOTYPE ROBOT USING AFTER MARKET COMPONENT AND PULSE WIDTH MODULATION (PWM) TECHNIQUE - Ahmad Rifai; Agung Wibowo (Universitas Bina Sarana Informatika Kota Sukabumi, 2016)
A robot is a machine that can perform task automatically or with guidance. Robotics is acombination of artificial intelligence and machines. Now robotics is fast growing andinteresting field and also can to cover deficiency human. One of defiency human can coverwith work principle obstacle avoider robot, example a blind people can used work principleobstacle avoider robot. This paper explain how to design a obstacle avoider robot with aftermarket parts (micro-controller ATmega 16 and IR sensor) to detect any obstacle ahead of itand sends a command to the microcontroller. This robot is controlled by a program thatimplanted to micro-controller so robot can take a decision itself whenever an obstacle comesin its path and it’s run well as expected.